Isolation and phylogenetic analysis of Staphylococcus aureus strains isolated from meat in traditional markets in Ha Noi - Quyen, Dong Van; Lanh, Pham Thi; Gahyun, Lee; Hoa, Nguyen Thi; Phuoc, Man Hong (Academia Journal of Biology, 2025)
Staphylococcus aureus is a major cause of foodborne illness worldwide, causing diarrhea and vomiting. The rising number of S. aureus food poisoning cases in Vietnam underscores the urgent need for effective control strategies, particularly given the bacterium’s growing antibiotic resistance, complicating treatment options. This study investigates the public health risks posed by S. aureus in meat samples collected from traditional markets in Hanoi, Vietnam. A total of 30 bacterial isolates were obtained, of which six were identified as S. aureus using MALDI-TOF MS and confirmed through hemolysis testing and 16S rRNA sequencing. These isolates exhibited strong beta-hemolysis, indicating alpha-toxin production and their pathogenic potential. Notably, the antibiotic susceptibility test revealed that some isolated strains displayed varying levels of resistance to commonly used antibiotics, including aztreonam, streptomycin, amoxicillin, amikacin, and enrofloxacin. However, their uniform susceptibility to florfenicol, ceftiofur, doxycycline, and chloramphenicol suggests that these antibiotics remain effective for treating S. aureus infections in this region. Phylogenetic analysis revealed a high degree of genetic similarity between the isolated strains and globally distributed S. aureus strains associated with foodborne outbreaks in India, Korea, Japan, and Brazil, highlighting the potential for international transmission. These findings highlight the need for ongoing surveillance, improved food safety measures, and the development of updated antibiotic treatment protocols to manage the risks of S. aureus in the food supply.